The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acsomega.8b00377
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemically Prepared Li2S–P2S5–LiBH4 Solid Electrolytes with an Argyrodite Structure

Abstract: Solid electrolytes with compositions of (100 – x )(0.75Li 2 S·0.25P 2 S 5 )· x LiBH 4 (mol %, 0 ≤ x ≤ 100) were mechanochemically prepared from the 75Li 2 S·25P 2 S 5 (mol %) glass and LiBH 4 crystal. The samples with x ≥ 43 have crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 32 publications
4
40
1
1
Order By: Relevance
“…(100 − x )(0.75Li 2 S‐0.25P 2 S 5 )‐ x LiBH 4 ( x ≤ 33) was synthesized through mechanical milling technique, where the electrolyte at x = 33 showed a Li + conductivity of 1.6 × 10 −3 S cm −1 at room temperature . When x = 50, the sample formed a crystalline phase of Li 6 PS 5 ·BH 4 and exhibited an even higher Li + conductivity of 1.8 × 10 −3 S cm −1 at room temperature . The favorable ionic conductivity of borohydride–sulfide combination might originate from the large anionic frameworks with high polarizability.…”
Section: Complex Hydrides As Solid‐state Electrolytementioning
confidence: 98%
“…(100 − x )(0.75Li 2 S‐0.25P 2 S 5 )‐ x LiBH 4 ( x ≤ 33) was synthesized through mechanical milling technique, where the electrolyte at x = 33 showed a Li + conductivity of 1.6 × 10 −3 S cm −1 at room temperature . When x = 50, the sample formed a crystalline phase of Li 6 PS 5 ·BH 4 and exhibited an even higher Li + conductivity of 1.8 × 10 −3 S cm −1 at room temperature . The favorable ionic conductivity of borohydride–sulfide combination might originate from the large anionic frameworks with high polarizability.…”
Section: Complex Hydrides As Solid‐state Electrolytementioning
confidence: 98%
“…18 Recent efforts have led to a variety of materials such as Li6PS5X ( = Cl, Br, and I), Li10MP2S12 ( = Ge and Sn), Li7P3S11, the Li2S-P2S5 glasses and many more fast ionic conductors, enabling the concept of all-solid-state battery (ASSB) to be realistic and comparable to the conventional Li-ion batteries. [19][20][21][22][23][24][25][26][27][28][29][30] The studies on all-solid-state Li-S batteries have become prominent after Hayashi et al reported operational all-solid-state Li-S batteries, employing mechanically alloyed Li2S-P2S5 glass-ceramic electrolyte. [31][32][33][34][35] In the early stage, a significant improvement in the performance has been achieved by processing the cathode composites via ball-milling, which was attributed to the intimate contact of the cathode components.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, while the conductivity of Li6PS5I5/6(BH4)1/6 was ameliorated, that of Li6PS5Br5/6(BH4)1/6 was reduced compared to the pure halide argyrodite, which can be explained by the local geometry constraints of the Li diffusion pathway. The conductivity of the Li6PS5BH4 synthesized by mechanochemical reaction is as high as 1.9 × 10−3 S cm−1 at RT [100]. The combination of the borohydride with sulphide and thio-sulphate compounds was also found to be appealing, resulting in a high ionic conductivity, a good electrochemical stability and compatibility with many electrode materials [101,102].…”
Section: Argyrodite Structure Materialsmentioning
confidence: 99%